GEOMETRIC TERMINOLOGY IN THE RUSSIAN LANGUAGE OF THE EARLY 17th CENTURY (EXEMPLIFIED BY “CHARTER OF MARTIAL, CANNON AND OTHER MATTERS RELATED TO MILITARY SCIENCE”) - Dmitry V. Rudnev; Milyausha G. Sharikhina (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The article examines linguistic means of representing geometric terminology in the Russian translated written records of the early 17th century “Charter of Martial, Cannon and Other Matters Related to Military Science”. The text of the military treatise Kriegsbuch (1573) by L. Fronsperger served as a source for the Russian text. The undertaken contrastive analysis of German and Russian texts resulted in the conclusion that Russian translators, when rendering German terms into Russian, mainly followed the strategy of domestication with the focus on the system of nominations that existed in the Russian language of that time. If there were correlated concepts in Russian, relatively stable ways of conveying them were used: Punct – stat’ya (article), Linie – cherta, chertezh (line), Winckel – ugol (angle), Tryangel – tregranets (triangle), etc. In the absence of equivalents, the translator could transliterate a foreign word and simultaneously use the words of the native language that are close in meaning: Diameter is expressed as diamet(e)r, razmer, mera. If the translator failed to give the appropriate Russian analogue or explanation, a word could have been omitted or rendered based on the information in the drawing (Centro, Hipotenusa, Cathetus, etc.). The lack of developed and generally accepted geometric terminology and models of scientific narration missing in the Russian language of the early 17th century hindered the translator’s striving for increased readability of the text.